A comment on Mendeş and Yiğit (2013), 'Type I error and test power of different tests for testing interaction effects in factorial experiments', Statistica Neerlandica, 67:1–26. (21st June 2013) - Shah, Denis A.; Madden, Laurence V.
Abstract : In their advocacy of the rank‐transformation (RT) technique for analysis of data from factorial designs, Mendeş and Yiğit ( Statistica Neerlandica, 67, 2013, 1–26) missed important analytical studies identifying the statistical shortcomings of the RT technique, the recommendation that the RT technique not be used, and important advances that have been made for properly analyzing data in a non‐parametric setting. Applied data analysts are at risk of being misled by Mendeş and Yiğit, when statistically sound techniques are available for the proper non‐parametric analysis of data from factorial designs. The appropriate methods express hypotheses in terms of normalized distribution functions, and the test statistics account for variance heterogeneity.